Divergent patterns in Indian Ocean trade to East Africa and southern Africa between the 7th and 17th centuries CE: The glass bead evidence - Marilee Wood (Afriques)
Glass beads form a large part of archaeological evidence attesting to Indian Ocean trade with eastern Africa between the 7th and 17th century CE, but they have generally been under-utilized by archaeologists in their efforts to understand and interpret that trade. Research in the past decade has identified seven bead series that were present in southern Africa during this time span, and chemical analysis has opened windows on the origins of the glasses used to make the beads. Together they facilitate the recreation of the changing trade patterns that will be explored here. In addition, the differences between the bead assemblages found on the northern and southern ends of the coast and the interior demonstrate that the two regions appear to have had different trade relations. The beads suggest that trade, or at least the trade in beads, to the south was never completely controlled by the north and at times may have been quite separate.